2014
DOI: 10.1002/jrsm.1122
|View full text |Cite
|
Sign up to set email alerts
|

Combining randomized and non‐randomized evidence in clinical research: a review of methods and applications

Abstract: Researchers may have multiple motivations for combining disparate pieces of evidence in a meta-analysis, such as generalizing experimental results or increasing the power to detect an effect that a single study is not able to detect. However, while in meta-analysis, the main question may be simple, the structure of evidence available to answer it may be complex. As a consequence, combining disparate pieces of evidence becomes a challenge. In this review, we cover statistical methods that have been used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 124 publications
(225 reference statements)
1
78
0
Order By: Relevance
“…Cross-design synthesis is a method that borrows information from observational data and combines it with trial data to extrapolate trial estimates to populations that were excluded from participation. 15,22 While the pivotal trial is enrolling participants, a cohort of users of the comparator treatment in the trial can be identified in observational healthcare data. When the trial is complete and ready for analysis, this cohort can be used to facilitate extrapolation of RCT findings.…”
Section: Review Of Methods To Generalize or Extrapolate Evidence Frommentioning
confidence: 99%
“…Cross-design synthesis is a method that borrows information from observational data and combines it with trial data to extrapolate trial estimates to populations that were excluded from participation. 15,22 While the pivotal trial is enrolling participants, a cohort of users of the comparator treatment in the trial can be identified in observational healthcare data. When the trial is complete and ready for analysis, this cohort can be used to facilitate extrapolation of RCT findings.…”
Section: Review Of Methods To Generalize or Extrapolate Evidence Frommentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51][52][53] These articles included two comprehensive reviews 44,45 as well as individual articles, all of which were identified in the review articles. Many of the techniques described in Verde and Ohmann 44 and Doi, 45 however, have limited applicability to regenerative medicine (i.e. when only limited evidence from a small number of studies is available), as they require significant numbers of studies or data from RCTs to be applied.…”
Section: Data Sharing Statementmentioning
confidence: 99%
“…A gentle introduction of this area can be found in Chap. 8 of Spiegelhalter et al [2] and a recent review in Verde and Ohmann [3].…”
Section: Introductionmentioning
confidence: 95%